2016
DOI: 10.1002/anie.201604730
|View full text |Cite
|
Sign up to set email alerts
|

A PCP Pincer Ligand for Coordination Polymers with Versatile Chemical Reactivity: Selective Activation of CO2 Gas over CO Gas in the Solid State

Abstract: A tetra(carboxylated) PCP pincer ligand has been synthesized as a building block for porous coordination polymers (PCPs). The air- and moisture-stable PCP metalloligands are rigid tetratopic linkers that are geometrically akin to ligands used in the synthesis of robust metal-organic frameworks (MOFs). Here, the design principle is demonstrated by cyclometalation with Pd(II) Cl and subsequent use of the metalloligand to prepare a crystalline 3D MOF by direct reaction with Co(II) ions and structural resolution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 76 publications
0
35
0
Order By: Relevance
“…A related approach to include reactive organometallic complexes was pursued by Humphrey et al 112,113 Seeking to achieve air and moisture stability, the researchers used a tetra(carboxylated) P-C-P pincer ligand to target highly connected, robust MOFs. Cyclometalation of the P-C-P pincer with Pd 2+ gave a metalloligand which could be used to prepare a crystalline 3D MOF (PCM-36, Phosphorus Coordination Material) with Co 2+ ions.…”
Section: (B) Mof Linker Matrix Isolationmentioning
confidence: 99%
“…A related approach to include reactive organometallic complexes was pursued by Humphrey et al 112,113 Seeking to achieve air and moisture stability, the researchers used a tetra(carboxylated) P-C-P pincer ligand to target highly connected, robust MOFs. Cyclometalation of the P-C-P pincer with Pd 2+ gave a metalloligand which could be used to prepare a crystalline 3D MOF (PCM-36, Phosphorus Coordination Material) with Co 2+ ions.…”
Section: (B) Mof Linker Matrix Isolationmentioning
confidence: 99%
“…Here, we report the greatly improved stability of a [Co 4 O 4 ] molecular cluster by covalent immobilization in a porous metal-organic framework. This strategy has allowed (i) significantly improved stability for a molecular OER catalyst (under practical, high pH conditions), and (ii) observation of a reactive, proposed (and otherwise unstable) intermediate in the OER mechanism (23)(24)(25)(26)(27)(28)(29)(30)(31). The organic linkers of these frameworks were optimized both for protection of the [Co 4 O 4 ] units from aggregation, and to provide electronic and structural tuning of reactivity (32)(33)(34).…”
mentioning
confidence: 99%
“…Instead, we explored the use of pre‐formed phosphine coordination complexes decorated with ancillary carboxylic acids (namely, approach 3). We showed that Pd II or Pt II complexes of carboxylated bis(phosphines) and PCP‐pincers, could be used to prepare porous PCMs with unique solid‐state reactivity. However, the multi‐step routes to prepare the precursors are complicated and large quantities are usually required in the search for optimal MOF‐forming conditions.…”
Section: Figurementioning
confidence: 99%